Effect of honey from Apis bee on blood glucose and insulin signaling proteins in skeletal muscle of streptozotocin-nicotinamide-induced diabetic rats / Yee Yong Mei - Yee, Yong Mei (2019)
Honey has been established as a potential anti-diabetic agent by lowering the blood glucose and protects against diabetes-induced damage on the vital organs. However, its effect on the skeletal muscle in diabetes is unknown. Hence, in this study, the effect of honey from Apis bee on the skeletal muscle expression of the insulin signalling proteins is investigated. Components of Apis bee honey were identified by liquid chromatography–mass spectrometry (LC-MS). Adult male rats were rendered diabetes via intraperitoneal injection of streptozotocin and nicotinamide (STZ-NA). Four days after STZ-NA injection Apis bee honey was administered orally by using oral gavage tube and confirmation of diabetes mellitus (T2DM). Apis bee honey treatment was given at 5 and 10 mg/kg bw once daily for 28 days. At the end of the Apis bee honey treatment, blood was withdrawn for plasma glucose analysis after overnight fasting (16 hours). Then rats were sacrificed via cervical dislocation and skeletal muscle was harvested for histology, immunohistochemistry (IHC)/ immunofluorescence (IF) and protein expression analysis by Western blotting (WB). flavonoids, phenolic acids, monosaccharides and fatty acids were present in the Apis bee honey. iv The compounds present at highest abundance include (i) flavonoids: (epi)afzelechin- (epi)catechin and isorhamnetin 3-O-rutinoside, (ii) phenolic acids: hydroxybenzoic acidO-hexoside and syringic acid-hexose and (iii) monosaccharide derivative: gluconic acid. Apis bee honey administration was found to lower the blood glucose level after 28 days in diabetic rats. Histological analysis indicates that Apis bee honey treatment ameliorated skeletal muscle pathological damage in diabetic rats where only minimal myofiber degeneration and mononuclear cellular infiltration were observed in skeletal muscle of Apis bee honey-treated diabetic rats. In the skeletal muscle, Apis bee honey treatment enhanced the expression of insulin signalling molecules insulin receptor β (IRβ), insulin receptor substrate 1 (IRS1), phosphoinositide 3-kinase (PI3K), protein kinase B (Akt) and glucose transporter 4 (GLUT4) in diabetic rats. These findings implied that Apis bee honey treatment to diabetic rats might enhance the insulin signal transduction via IRβ/IRS1/PI3K/Akt pathway that can help to augment the GLUT4 expression, thereby improving the glucose uptake in the skeletal muscle of diabetic rats. These effects could either be directly or indirectly via improving the hyperglycemia in diabetic rats, where this needs to be further confirmed. It can also be postulated that phenolic compounds with antioxidant and antiinflammatory properties in Apis bee honey, such as (epi)afzelechin-(epi)catechin and isorhamnetin 3-O-rutinoside, might be responsible for these effects. This study thus suggests the usefulness of Apis bee honey as an agent to manage diabetes.